Methods for the assessment of structural integrity of components and structures - Lidbury, David P. G.; Hirsch, P. B. (Maney, for the Institute of Materials, Minerals and Mining, 2003)
This volume brings together the papers presented at the 8th Symposium organised by the Technical Advisory Group on Structural Integrity of Nuclear Plant (TAGSI), which was held on 25 April 2001 at the TWI Conference Centre at Granta Park, Great Abington near Cambridge, UK. The subject of this one-day symposium was "Methods for the Assessment of the Structural Integrity of Components and Structures" and was attended by over eighty delegates from nuclear and non-nuclear industries, academia and governmental organisations. The construction, process, power generation, manufacturing and tr.
"Papers presented at the 8th symposium organised by the Technical Advisory Group on Structural Integrity of Nuclear Plant (TAGSI), held on 25th April 2001 at ... Great Abington near Cambridge."--Foreword.
Keywords: Structural analysis (Engineering) -- Congresses.; Fracture mechanics -- Congresses.; Materials -- Fatigue -- Congresses.; elektronické knihy; electronic books